ANALISIS TINGKAT KESEHATAN BANK UMUM SYARIAH BERDASARKAN METODE RGEC RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, AND CAPITAL PADA PT. BANK MUAMALAT INDONESIA - Jumriaty Jusman (Jurnal Ilmu Ekonomi dan Bisnis, 2019)
Abstract: This research was conducted on the basis of observations of events that occurred at PT. Bank Muamalat Indonesia, where the bank is spread, issues will experience liquidity. So the purpose of this study is to determine the health level of PT. Bank Muamalat Indonesia using the RGEC method (risk profile, good corporate governance, earnings and capital) for the 2015-2017 period. This research will be conducted by collecting data in accordance with the provisions stipulated in Bank Indonesia regulations No.13 / 1 / PBI / 2011 and SE No.13 / 24 / DPNP. The research subject in this study was PT Bank Muamalat Indonesia, Tbk. The object of this research is the financial statements and publications of PT Bank Muamalat Indonesia, Tbk 2015-2017 period. The results of the study showed that the health level of Bank Muamalat Indonesia using RGEC showed the predicate of bank health in accordance with the standards set by Bank Indonesia, with the results of financial ratios obtained from annual reports adjusted to the RGEC Component Ranking Criteria Matrix (Risk Profile, Good Corporate Governance , Earning and Capital) and the calculation of the final composite value on average 60%, it can be concluded that PT. Bank Muamalat Indonesia in 2015-2017 ranked 4 (four) with the title